A Life Course Perspective on Health Trajectories and Transitions - Burton-Jeangros, Claudine; Cullati, Stéphane; Sacker, Amanda; Blane, David (Life Course Research and Social Policies, 2015)
Public Health; Sociology, general; Epidemiology